The Effects of Diet, Physical Activity, and Social Support on Overweight and Obesity in Female Adolescents - Yeti Rahelli; Agus Kristiyanto; Bhisma Murti (Journal of Health Promotion and Behavior, 2020)
Background: Obesity is reaching global epidemic proportions with a threefold increase from 1975-2016. The percentage of adolescents aged 12-19 years old who are obese has increased from 5% -21% in the same period. The SCT can determine dietary behavior and regular physical activity. Study shows that a healthy diet, regular activity and social support contribute to weight gain. This study aims to estimate the effect of diet, physical activity, social support on overweight girls.Subjects and Method: This study was an observational analytic study with a cross sectional design. The sample size was 120 study subjects using stratified random sampling. Data analysis with path analysis using the Stata 14 program.Results: Overweight/ obesity was directly reduced by healthy diet (b= -3.62; 95% CI= -5.08 to -2.15; p<0.001), healthy behavior (b= -2.02; 95% CI= -3.40 to -0.67; p= 0.003), and high physical activity (b= -1.74; 95% CI= -3.40 to -0.10; p= 0.038). Overweight/ obesity was indirectly affected by vicarious learning, maternal education, family income, and family support.Conclusion: Overweight/ obesity is directly reduced by healthy diet, healthy behavior, and high physical activity. Overweight/ obesity is indirectly affected by vicarious learning, maternal education, family income, and family supportKeywords: diet, physical activity, family support, SCT, path analysisCorrespondence: Yeti Rahelli. Master of Public Health Sciences, Universitas Sebelas Maret. Jl. Ir. Sutami No. 36A Kentingan Surakarta 57126, Central Java, Indonesia. Email: yetirahelli@student.uns.ac.idJournal of Health Promotion and Behavior (2020), 05(03): 209-220https://doi.org/10.26911/thejhpb.2020.05.03.07